2020
DOI: 10.3390/microorganisms8091275
|View full text |Cite
|
Sign up to set email alerts
|

Biosulfidogenesis Mediates Natural Attenuation in Acidic Mine Pit Lakes

Abstract: Acidic pit lakes are abandoned open pit mines filled with acid mine drainage (AMD)—highly acidic, metalliferous waters that pose a severe threat to the environment and are rarely properly remediated. Here, we investigated two meromictic, oligotrophic acidic mine pit lakes in the Iberian Pyrite Belt (IPB), Filón Centro (Tharsis) (FC) and La Zarza (LZ). We observed a natural attenuation of acidity and toxic metal concentrations towards the lake bottom, which was more pronounced in FC. The detection of Cu and Zn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 97 publications
(157 reference statements)
2
24
0
Order By: Relevance
“…Sulfate-reducing prokaryotes can be detected in environmental samples by the presence of two conserved genes; dissimilatory (bi)sulfide reductase (dsrAB) and adenosine-5'-phosphosulfate reductase (apsA; Wagner et al, 2005), with dsrAB used as a phylogenetic marker for sulfate-reduction (Müller et al, 2015). Sulfate-reduction can occur at a wide range of pH values, from pH 2.5-4.0 (Florentino et al, 2019;Sánchez-Andrea et al, 2013;van der Graaf et al, 2020), to pH 11 in soda lakes (Sorokin et al, 2011). Stimulating sulfate reduction is beneficial as contaminant metals can be precipitated as insoluble sulfide minerals and it also generates alkalinity that helps to treat acidic mine waters (Guy Riefler et al, 2008).…”
Section: Reduction Processes and Their Impact On Metal Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfate-reducing prokaryotes can be detected in environmental samples by the presence of two conserved genes; dissimilatory (bi)sulfide reductase (dsrAB) and adenosine-5'-phosphosulfate reductase (apsA; Wagner et al, 2005), with dsrAB used as a phylogenetic marker for sulfate-reduction (Müller et al, 2015). Sulfate-reduction can occur at a wide range of pH values, from pH 2.5-4.0 (Florentino et al, 2019;Sánchez-Andrea et al, 2013;van der Graaf et al, 2020), to pH 11 in soda lakes (Sorokin et al, 2011). Stimulating sulfate reduction is beneficial as contaminant metals can be precipitated as insoluble sulfide minerals and it also generates alkalinity that helps to treat acidic mine waters (Guy Riefler et al, 2008).…”
Section: Reduction Processes and Their Impact On Metal Mobilitymentioning
confidence: 99%
“…Sulfate-reduction can occur at a wide range of pH values, from pH 2.5 -4.0 (Florentino et al, 2019;Sánchez-Andrea et al, 2013;van der Graaf et al, 2020) and to up to pH 11 in soda lakes (Sorokin et al, 2011). Stimulating sulfate reduction is beneficial as contaminant metals can be precipitated as insoluble sulfide minerals and it also generates alkalinity that helps to treat acidic mine waters (Riefler et al, 2008).…”
mentioning
confidence: 99%
“…Such waters represent an extreme environment for life but also a unique ecological niche for metabolically active acidophilic bacteria that are well adapted to the multiple environmental stresses encountered. Some of these microorganisms directly respond to contamination and favor natural metal attenuation through direct control of biomineralization processes, or favoring compartmentalized response to stress, and then the evolution of the system itself ( Lawrence et al, 1998 ; De Giudici et al, 2017 ; van der Graaf et al, 2020 ; Newsome et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the recent literature expanded the Zn concentration limits, toxic to sulfate reducers, from 210 mg/l ( Radhika et al, 2006 ) up to 450 mg/l ( Sánchez-España et al, 2020 ), the physicochemical limits enabling SRB to be active are still under study. For instance, van der Graaf et al (2020) suggested that in the acidic La Zarza pit lake, with Zn concentrations exceeding 500 mg/l, elemental sulfur reduction and disproportionation of S 8 0 are the dominant processes, while the sulfate reduction starts at a later stage of the natural bioremediation, when the metal attenuation is already triggered.…”
Section: Introductionmentioning
confidence: 99%
“…This, for several reasons, some, fundamental and related with the search for the limits of life [ 2 ], and others, more pragmatic and focused on the biotechnological potential of extremophiles, has sparked a marked growth of interest in the ecology of extreme environments [ 3 ]. The 2019–2020 version of Extremofiles 2.0, a Special Issue of Microorganisms devoted to extremophiles, has gathered eleven papers dealing with different aspects of microorganisms that thrive in extreme environments: five on halophiles [ 4 , 5 , 6 , 7 , 8 ], three on acidophiles [ 9 , 10 , 11 ], one on thermophiles [ 12 ], one on psycrophiles [ 13 ] and one on metal resistant microorganisms [ 14 ].…”
mentioning
confidence: 99%